Association of Abdominal Volume Index with Asymptomatic Intracranial Arterial Stenosis in Rural Chinese Adults: A Population-Based Study - Qiuting Wang; Xinhao Yang; Zhengyu Yang; Xinyan Hu; Jiehong Yuan; Maoyu Li; Xiaotong Ma; Xiang Wang; Chengxuan Qiu; Qinjian Sun (Obesity Facts)
Introduction: The abdominal volume index (AVI), a novel anthropometric index that reflects abdominal obesity, has been related to atherosclerosis. We sought to investigate the association of AVI with the severity and burden of asymptomatic intracranial arterial stenosis (aICAS) in a rural Chinese population. Methods: The population-based cross-sectional study included 1,994 participants who were aged ≥40 years and living in Kongcun Town, Pingyin County, Shandong, and who had no history of clinical stroke or transient ischemic attack. We detected aICAS by combining transcranial Doppler ultrasound with magnetic resonance angiography. We used multiple logistic regression models to investigate the association between AVI and aICAS. Results: Of the 1,994 participants, 146 were diagnosed with aICAS, including 51 with mild aICAS and 95 with moderate-to-severe aICAS. Controlling for confounding factors, a greater AVI was significantly associated with an adjusted odds ratio (OR) (95% confidence interval [CI]) of 1.08 (1.02–1.14) for having aICAS, 1.11 (1.04–1.18) for moderate-to-severe aICAS, and 1.12 (1.01–1.23) for multiple moderate-to-severe aICAS. We detected a statistical interaction of AVI with hypertension on aICAS (p for interaction = 0.011). Stratified analysis by hypertension showed a significantly independent association between AVI and aICAS in participants with hypertension (upper versus lower tertile of AVI: OR = 2.90; 95% CI: 1.65–5.10, p < 0.001) but not in those without hypertension. Conclusion: A greater AVI is independently associated with aICAS, especially among individuals with hypertension. Moreover, AVI may help to identify both the severity and burden of aICAS.